A GROUNDED THEORY STUDY FOR ANTENATAL CARE IN KENYA - Owino, Joyce; Legault, Frances; Mumbo, Hazel Miseda; Odera, Odhiambo; Ayugi, Mary Evelyn (European Scientific Journal, ESJ, 2013)
The purpose of the study was to analyze nurse–client interaction processes in rural health facilities. This was an inductive, qualitative, grounded theory study. Constant comparative analysis of data was used to generate themes, concepts and theoretical statements. Six main concepts emerged from data: Willingness of mother to attend antenatal clinic, reciprocal exchange of information, nursing care and treatment, focused preparation of mother, evaluating readiness for delivery within the rural context and referral of client. These concepts were key to the generation of “Owino’s theory of nurse-client interactions for childbirth preparedness”. Nurse-client interaction processes in preparation for delivery by a skilled attendant is influenced by the complex rural context. High quality interaction should help the nurse and mother rise above contextual challenges.